Sex differences in reactive driving with aging - Zablocki, Victoria, author; Lodha, Neha, advisor; Tracy, Brian L., committee member; Malcolm, Matthew P., committee member (Colorado State University. Libraries, 2018)
Driving is a complex task that requires integration of perceptual and motor abilities. Age-related changes in perceptual motor abilities contribute towards driving deficits in older adults. Whether driving deficits in older adults are influenced by sex-differences is unknown. Purpose: Therefore, the purpose of this study was 1) to determine sex differences in reactive driving performance with advancing age and 2) to identify the differences in reactive driving strategies between older males and females. We tested reactive driving performance in a simulated environment that focuses on reactive driving. Reactive driving is a key component of car following task and involves responding to an unexpected environmental stimuli with fast and precise movements. Methods: Older male (N=12; age= 65.18 ± 7.19 yrs.) and older female (N=12; age= 66.25± 11.96 yrs.) adults performed a reactive driving task. All participants were right limb dominant and performed the simulated driving task with the right leg. We quantified reactive driving performance with the total response time, as the time from the onset of visual stimulus (brake lights of the car ahead) to application of brake force. To determine the contribution of perceptual ability (visual information processing speed), we quantified the pre-motor response time as the time from the onset of the visual stimulus to the activation of tibialis anterior. To determine the contribution of the motor ability (movement preparation and execution speed) to reactive driving performance, we quantified the motor response time as the time from the activation of tibialis anterior to the brake force onset. Results: The total response time was not significantly different between older male and older female adults (|t22| = -.17; p > 0.05). The pre-motor response time was significantly longer in older females as compared with the older males (|t22| = 2.91; p < .01). In contrast, the motor response time was significantly shorter in older females compared with the older males (|t22| = -2.52; p < .01). The group differences in premotor and motor response times were not influenced by strength or motor variability. Conclusion: Older male and older female adults demonstrate comparable total response time on a reactive driving task. These findings suggest an absence of sex related differences in reactive driving with advancing age. This study provides novel evidence that older male and female adults adopt different strategies for reactive driving. While older males show reduced speed of movement preparation and execution compared with older females, older females show reduced speed of visual information processing relative to older males. Thus, driving rehabilitation must focus on targeting sex specific deficits for enhancing driving function in older adults.